2012
DOI: 10.3389/fnins.2012.00088
|View full text |Cite
|
Sign up to set email alerts
|

Visually Guided Decision Making in Foraging Honeybees

Abstract: Honeybees can easily be trained to perform different types of discrimination tasks under controlled laboratory conditions. This review describes a range of experiments carried out with free-flying forager honeybees under such conditions. The research done over the past 30 or so years suggests that cognitive abilities (learning and perception) in insects are more intricate and flexible than was originally imagined. It has become apparent that honeybees are capable of a variety of visually guided tasks, involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 84 publications
0
29
0
Order By: Relevance
“…Extensive behavioral studies have shown that honeybees perceive, learn and memorize colors, shapes and patterns when these visual cues are paired with sucrose reward and that they navigate in their environment using visual cues to find their way back to the hive and to the food sources (Menzel and Backhaus, 1991; Srinivasan, 1994, 2011; Giurfa and Menzel, 1997; Dyer, 2012; Zhang et al, 2012; Avarguès-Weber and Giurfa, 2014). Furthermore, landmarks and celestial cues such as azimuthal position of the sun and polarized light pattern of the sky ensure efficient navigation in a complex environment (Wehner and Rossel, 1985; Rossel and Wehner, 1986; Collett et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive behavioral studies have shown that honeybees perceive, learn and memorize colors, shapes and patterns when these visual cues are paired with sucrose reward and that they navigate in their environment using visual cues to find their way back to the hive and to the food sources (Menzel and Backhaus, 1991; Srinivasan, 1994, 2011; Giurfa and Menzel, 1997; Dyer, 2012; Zhang et al, 2012; Avarguès-Weber and Giurfa, 2014). Furthermore, landmarks and celestial cues such as azimuthal position of the sun and polarized light pattern of the sky ensure efficient navigation in a complex environment (Wehner and Rossel, 1985; Rossel and Wehner, 1986; Collett et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Among insects, the honeybee has emerged as a powerful model for the study of associative learning [12,14,15,[19][20][21]. In a natural context, bees learn and memorize the local cues characterizing the places of interest, which are essentially the hive and the food sources [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Bees perceive and discriminate various types of visual cues and exhibit sophisticated visually driven behaviours [25,28,29]. A traditional view of insect vision posits that bees perceive only low-level, local visual cues and are incapable of global, holistic perception [30,31] (but see [26,27,29,32]).…”
Section: Introductionmentioning
confidence: 99%
“…The honeybee Apis mellifera is a privileged invertebrate model for the study of visual perception [24][25][26][27][28]. Bees perceive and discriminate various types of visual cues and exhibit sophisticated visually driven behaviours [25,28,29].…”
Section: Introductionmentioning
confidence: 99%